Perlindungan Data Pribadi di Era Digital: Tantangan dan Solusi Dalam Sistem Perbankan - Rahmadani, Ardita Esti; Pangestu, Yoga; Halizhah, Nur (Media Hukum Indonesia (MHI), 2024)
This article discusses the challenges and solutions for personal data protection in the banking sector in the digital era. Advances in information technology provide ease of access but also increase the risk of data security breaches, including hacking, identity theft, and privacy violations. This study uses a descriptive-analytical approach with qualitative methods to explore the main challenges faced by banks and the solutions that can be applied, such as encryption technology, intrusion detection and prevention systems, and digital literacy education programs for customers. With this approach, the article presents policy and technological recommendations for the banking sector to enhance customer data security in Indonesia.